EFFECTS OF TURBULENCE-RADIATION INTERACTIONS IN A NON-PREMIXED TURBULENT METHANE-AIR FLAME - Lemos, L. D.; Centeno, F. R.; França, F. H. R. (Revista de Engenharia Térmica, 2018)
This work studied a turbulent flame and analyzed the interaction between turbulence and radiation (TRI). The problem consists of a non-premixed turbulent methane flame surrounded by a low-velocity air coflow identified as Flame DLR-A. The steady laminar diffusion flamelet (SLDF) model is used to solve the chemical kinetics. To generate the flamelet library, turbulence-chemistry interaction is taken into account through previously assumed probability density functions (PDF) of mean scalars. Radiative heat flux is calculated with the discrete ordinates method, considering the Gray Gas model (GG). Turbulence is solved with k-ε Standard model and TRI methodology is based on temperature self-correlation. The solution is obtained using ANSYS/Fluent code coupled with user-defined functions (UDFs). Results indicated that the temperature and chemical species predictions are little affected by TRI, while the radiative quantities (radiative heat flux on the domain wall) are importantly affect by TRI effects.